Variation in Adenoma Detection Rate and the Lifetime Benefits and Cost of Colorectal Cancer Screening: A Microsimulation Model - Meester, Reinier G.S. (JAMA, 2015)
IMPORTANCE: Colonoscopy is the most commonly used colorectal cancer screening test in the United States. Its quality, as measured by adenoma detection rates, varies widely between physicians with unknown consequences for the cost and benefits of screening programs. OBJECTIVE: To estimate the lifetime benefits, complications and costs of a colonoscopy screening program at different levels of adenoma detection. DESIGN, SETTING AND PARTICIPANTS: This study used microsimulation modeling with data from a community-based healthcare system on adenoma detection rate variation and cancer risk among 136 physicians and 57,588 patients for 1998–2010. EXPOSURE: Using modeling, no screening was compared to screening initiation with colonoscopy according to adenoma detection rate quintiles (averages 15.3, 21.3, 25.6, 30.9, and 38.7%) at ages 50, 60 and 70 with appropriate surveillance of adenoma patients. MAIN OUTCOMES: Estimated lifetime colorectal cancer incidence, mortality, number of colonoscopies, complications and costs per 1,000 patients, all discounted at 3% per year and including 95% confidence intervals from multiway probabilistic sensitivity analysis (95%CI). RESULTS: In simulation modeling, among unscreened patients, the lifetime risks of colorectal cancer incidence and mortality were 34.2 (95%CI:25.9–43.6) and 13.4 (95%CI:10.0–17.6) per 1,000, respectively. Among screened patients, simulated lifetime incidence decreased with lower to higher adenoma detection rates (quintile 1 versus 5: 26.6, 95%CI:20.0–34.3 versus 12.5, 95%CI:9.3–16.5) as did mortality (5.7, 95%CI:4.2–7.7 versus 2.3, 95%CI:1.7–3.1). Compared to quintile 1, simulated lifetime incidence and mortality were on average 11.4% (95%CI:10.3–11.9) and 12.8% (95%CI:11.1–13.7) lower, respectively, for every 5 percentage-point higher adenoma detection rate. Total colonoscopies and associated complications were higher from quintile 1 (2,777, 95%CI:2,626–2,943 and 6.0, 95%CI:4.0–8.5) to subsequent quintiles (quintile 5: 3,376, 95%CI:3,081–3,681 and 8.9, 95%CI:6.1–12.0). Estimated net screening costs were, however, lower from quintile 1 (US $2.1 million, 95%CI:1.8–2.4) to quintile 5 (US$1.8 million, 95%CI:1.3–2.3) due to averted cancer treatment costs. Results were stable across sensitivity analyses. CONCLUSIONS-RELEVANCE: Using microsimulation modeling, we found that higher adenoma detection was associated with lower lifetime colorectal cancer incidence and mortality without higher overall costs. Future research is needed to assess if increasing adenoma detection would be associated with improved patient outcomes.